DETERMINAN AUDITOR OPINION ON GOING CONCERN PADA PERUSAHAAN MANUFAKTUR DAN PERTAMBANGAN TERDAFTAR PADA BURSA EFEK INDONESIA - Darmansyah, - (L2Dikti Wilayah III, 2020)
The practices of tax avoidance that occur in Indonesia are very detrimental to the state. Based on data from Global Financial Integrity, Indonesia is ranked ninth from the most disadvantaged countries due to the exit money. The potential losses experienced by Indonesia are estimated at USD 180 billion from inconsistent transactions including avoiding taxes transactions. This research aimed to analyze and obtain empirical evidence on the relationship profitability, liquidity, leverage, and company size flow on acceptance going concern audit opinion. Data used in this research were obtained through documentation from data which gathered in Indonesian Stock Exchange (IDX). The sample method used in this research is purposive sampling with regression logistic analysis in manufacturing and mining firms which registers on period 2012 until 2016. The results of this research have found that profitability and leverage have relationship significantly negative toward going concern audit opinion. While liquidity and company size have no relationship toward going concern audit opinion.